Absentee Land Management Policy by Civil Servants - Endang Ristianti (Sultan Agung Notary Law Review, 2021)
This study aims to examine and analyze: 1) Implementation and Policy of Absentee Land Management by Civil Servants at the Land Office of Klaten Regency. 2) Implementation and Policy of Absentee Land Management by Civil Servants at the Klaten Regency Land Office. The approach method used in this research is the Normative approach. Normative legal research or library research is research that examines document studies, which uses various secondary data such as statutory regulations, court decisions, legal theory, and can be in the form of scholars' opinions. The research specification used is descriptive analytical. In this study, the data source consisted of primary data obtained by researchers through interviews and secondary data obtained through literature studies. Based on the results of the study, it can be concluded that: 1) Implementation of the implementation of absentee ownership of agricultural land obtained by Civil Servants provides opportunities for Civil Servants to be able to own the Absentee land. The legal instrument that regulates the ownership of Absentee land by Civil Servants/PNS is Government Regulation Number 4 of 1977 as described in the provisions of Article 2 paragraph (1), Article 2 paragraph (2), Article 2 paragraph (3) and Article 2 paragraph (4) Government Regulation Number 4 Of 1977. As for the implementation of absentee ownership of agricultural land in Klaten Regency, with the provision that a maximum distance of 8 km is stipulated for absentee land, if it exceeds 8 km then the implementation cannot be fulfilled. 2) Constraints in the Absentee Land Management Policy by Civil Servants at the Klaten Regency Land Office stem from community factors, namely the lack of legal awareness from the community Community life can run in an orderly and orderly manner, of course supported by an order so that life becomes orderly. Therefore, socialization plays an important role in the implementation of the Absentee Land Management Policy by Civil Servants at the Klaten Regency Land Office.